O apoio no processo parturitivo : vivência de puérperas e acompanhantes - Moura, Daniele Cristie de (2020)
This study aimed to analyze the support offered by companions to women during the parturition process in a Pre-delivery / Childbirth / Puerperium unit of a university hospital in the city of Cuiabá-MT. This is a study with a qualitative and descriptive approach. The data construction process was carried out through participant observation of vaginal deliveries, where the women were with a companion, later open interviews were conducted with the puerperal women and the companions, in all, 22 participants (11 women and 11 companions). The analysis of empirical data followed Minayo's proposal through content analysis in the thematic modality. After the thematic analysis of the empirical material, the following categories emerged: The support offered by the companion in the context of vaginal delivery and Possibilities / limits for the realization of the support provided by the companion in the parturitive context. In the first category, it was evidenced that the companions developed the dimensions of emotional and physical support and that the dimensions of informational support and rights were not explored by the companions in a relevant or significant way. It is understood that both dimensions require from the companion some information about the delivery process, and factors such as the lack of prior preparation are related to the absence of these dimensions of support in the context of this study. The second category refers to the conditions that interfered with the development of support by the companions. As facilitating conditions, there is the performance of the PPP sector team of the hospital under study, especially obstetric nurses, who acted in order to encourage the inclusion of the companion in the parturition process, through attitudes such as welcoming and clarifying doubts. As barriers to the development of support by companions in the parturition process, prenatal unpreparedness was observed, which was expressed through: the lack of awareness / preparation of pregnant women to choose a companion, assistance focused on the biological aspects of pregnancy, absence of space for qualified listening, lack of educational activities. Also with regard to this category, it was observed that the participants were not given the opportunity to know the reference maternity before delivery, and the ignorance of the rights of the pregnant woman. The contributions of the present study reaffirm the relevance of the support offered by the companion to the parturients, emphasizing the potential of these subjects to offer security and tranquility to women. It was also noticed that, in the context of the present study, the potential of these subjects was not fully explored, since in order to exercise all dimensions of support, a previous theoretical contribution is necessary, which was absent in the reality of the participants. In view of these facts, it is expected that this study will contribute to future discussions despite the importance of the support offered by companions in the parturition process as well as the importance of strengthening prenatal strategies in order to include the pregnant woman's family in this process.